Modeling of reactant concentration in electrocatalytic processes at conducting polymer modified electrodes - Jasaitis, Valdas; Malinauskas , Albertas; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2007)
This research presents a mathematical model analyzing of electrochemical processes occurring at electrodes covered with a thin film of a conducting polymer. The model takes into account the diffusion of solution species into a polymer film, diffusion of charge carriers within the film, and a chemical redox reaction within the film. The aim of this work was to find the location of a mean reaction zone that is of a great practical interest related to optimization of the parameters of electrocatalytic system for its best performance. It has been shown that electrocatalysis of solute species at conducting polymer modified electrodes proceeds within the polymer film rather than at he outer polymer/solution interface.
Keywords: modeling; electrocatalysis; reaction-diffusion; conducting polymer